2023
DOI: 10.3390/agriculture13010146
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soybean to Selected Abiotic Stresses—Photoperiod, Temperature and Water

Abstract: The sharp increase in soybean (Glycine max (L.) Merrill) acreage in the late 20th century and early 21st century is due to the demand for edible oil and feed protein. However, a limiting factor in the extent of soybean cultivation is its high heat requirements and response to photoperiod. Most varieties are short-day plants and are generally the best-yielding genotypes. At higher latitudes (longer day length), there is a delay in the occurrence of subsequent developmental stages and problems with plant maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 227 publications
(309 reference statements)
0
8
0
Order By: Relevance
“…Low-temperature stress from germination to emergence, which is a sensitive period of soybean growth, can affect protein and cell membrane metabolism adversely. This kind of damage can cause the elongation of soybean stems to encounter obstacles, thereby affecting the flowering period [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Low-temperature stress from germination to emergence, which is a sensitive period of soybean growth, can affect protein and cell membrane metabolism adversely. This kind of damage can cause the elongation of soybean stems to encounter obstacles, thereby affecting the flowering period [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The developed model image showed that it enables improved interpretation according to some garlic individuals in the visualization of stress detection of garlic. Non-biological stresses such as high-temperature and soil moisture stress can cause nonlinear changes in the spectral characteristics of plants [ 64 , 65 ]. Linear models such as PLS-DA assume a linear relationship between spectral data as an independent variable and non-biological stress as the dependent variable in this study, which is the complex nonlinear relationship present in the data [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soybeans are in the top 5 important food crops around the world ( Savary et al., 2019 ), which is mostly due to their essential amino acid composition and complete protein content ( Michelfelder, 2009 ). There have been many studies investigating the physiological and/or biochemical effects of flooding on soybeans ( Khan et al., 2021 ; Komatsu et al., 2021 ; Staniak et al., 2023 ; Wang and Komatsu, 2018 ; Zhou et al., 2021 ), but few studies have investigated the shifts of its microbial communities ( Lian et al., 2023 ; Yu et al., 2022 ). For example, it has been shown that flooding stress creates signaling for cell death and proteolysis in the root tips ( Yanagawa and Komatsu, 2012 ; Nanjo et al., 2013 ), along with diminished root elongation and hypocotyl pigmentation ( Hashiguchi et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%